Educational Contributions in Family and Participative Extracurricular on Students' Prosocial Behavior - Nur Hasanah Harahap; Daharnis Daharnis; Syahniar Syahniar (International Journal of Research in Counseling and Education, 2020)
This research was to describe the educational contribution in family and about being active while participating extracurricular on prosocial behavior of students in SMK Negeri 6 Padang. This research applied descriptive quantitative method. The population was 903 students in X and XI grade at SMK Negeri 6 Padang and 278 students as the sample were selected using proportional random sampling techniques. The instruments used was questionnaire. The data were analyzed with regression statistics, simple and double regressions. The data analysis was assisted using the SPSS 20.0 program. The study showed that: (1) the average of prosocial behavior was in the high category, (2) education in family was in the high category, there were 28% contribution of education in family to prosocial behavior, (3) the activity in participating extracurricular was in the high category, there were 16.2% contributions of activeness to participate in participative extracurricular on students’ prosocial behavior, (4) there were 31.5% contributions of both educational contribution in family and participative extracurricular on students’ prosocial behavior.